The answer is B. 5
6+2=8
3+5=8
<u>6
</u>13.20
Divide by 6
<u>1
</u>2.2
Answer: x = - 3.5
Step-by-step explanation:
Rewrite the equation by completing the square.
4x2 + 28x + 49 = 0
Completing the square method :
Divide through by the Coefficient of x^2
x^2 + 7x + (49/4) = 0
a = 1, b = 7, c = 49/4
Move c to the right side of the equation
x^2 + 7x = - 49/4
Complete the square on the left hand side by squaring its half of the x term
(7/2)^2 = (49/4)
Add the output to both sides of the equation
x^2 + 7x + (49/4) = - (49/4) + (49/4)
(x + 7/2)^2 = 0
Square root of both sides
x + 7/2 = 0
x = - 7/2
x = - 3.5
Answer:
Step-by-step explanation: x - 6
The given equation can be re-written as y = ---------
-3
Arbitrarily choose x = 0. Then:
x - 6 0-6
y = --------- = ----------- = 2, so (0, 2) is a point on the graph which is also the
-3 -3 y-intercept
Arbitrarily choose x = 6. Then y = 0, and (6, 0) is another point on the graph
which happens to be the x-intercept
arbitrarily choose x = 12. Then y = (12 - 6) / (-3) = -2. Then (12, -2) is
another point on the
graph.
Plot (12, -2), (6, 0) and (0, 2). Draw a line through these three points.
5. -6a-48
6. 36x+4
7. 30n+40
8. 1.8m+2
Yess